Analysis Of The Effect Of Intellectual Capital And Good Corporate Governance On The Financial Performance Of Sharia Commercial Banks (2017-2021 Period) - Abdillah Aswari; Andri Soemitra; Muhammad Ikhsan Harahap (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
This study aim to determin the effect ofintelectual capital and good corporate governanc on the financial performance of Islamic commercial bank. This type of research is a quantitative research with secondary data sources used. This study uses data from the annual financial reports of Islam commercial banks for 2017-2021. The research sample is Islamic Commercial Banks in Indonesia in 2017-2021. The sample was selected using a purposive sampling technique in order to obtain eight Islamic Commercial Banks. Processing techniques and data analysis using Descriptive Statistical Analysis, Multiple Linear Regression Analysis, Classical Assumption Test and Hypothesis Test. The program used for calculations uses SPSS version 25 which then interpres the results from SPSS. The results of the study show that the intellectual capital variable has a significan efect on financial performance. Meanwhile, the variables of institutional ownership andmanagerial ownership have no significant effect the financial performance of Islamic Commercial Bank.